Q-switched pulse generation in erbium-based with niobium aluminium carbide saturable absorber - Nurul Athirah Mohamad Abdul Ghafar; Arni Munira Markom; Ahmad Haziq Aiman Rosol; Nur Farhanah Zulkipli; Suziana Omar; Ahmad Razif Muhammad; Hazlihan Haris; Ismail Saad; Sulaiman Wadi Harun (Semarak Ilmu, 2024)
The viability of using Niobium Aluminum Carbide (Nb2AlC) as a saturable absorber (SA) for Q-switched pulse production utilized in erbium arrangement is reported in this research. Polyvinyl alcohol (PVA) and the MAX phase material Nb2AlC were successfully mixed to create a SA film, which was then placed between two fiber ferrules and inserted into the cavity. Steady Q-switched pulses at 1531 nm with a maximum repetition rate of 58.21 kHz and a minimum pulse width of 3.82 s were seen after raising the pumping power from 45.45 to 81.97 mW. The highest pulse energy was measured to be 42.26 nJ at a pump power of 81.97 mW. These findings show that Nb2AlC MAXphase material can be used to make SAs that are both useful and affordable.